Analisis Finansial Usahatani Serai Wangi (Cymbopogon Nardus L.) Di Kota Solok (Studi Kasus : Kelompok Tani Kalumpang Saiyo) - Muhammad Farrasky Delas Putra; Ahmad Fachri (Jurnal Adminitrasi Bisnis Nusantara, 2023)
Citronella grass (Cymbopogon Nardus L.) as an essential plant is one of the potential agroindustry export commodities that can be one of top essential oils for Indonesia to earn foreign exchange. This study aims to analyze the citronella grass finance farming by using B / C Ratio, Net Present Value, Internal Rate of Return and Payback Period at 9% interest rate. The method used in this research is case study. The sampling method is purposive sampling, where The farmer groups are selected based on certain criteria. Data analysis used in this research is descriptive quantitative, intended to determine the financial feasibility of citronella farming using investment criteria in the form of B/C Ratio, Net Present Value, Internal Rate of Return and Payback Period. From research of investment criteria, it is found that citronella grass in Kalumpang Saiyo Farmer group is feasible to be implemented, with B / C Ratio value equal to 1,23, NPV value equal to Rp 73.809.351,96, -, IRR 83,89% Payback Period 4 years 5 months 7 days.